Munchausen by Internet: Current Research and Future Directions - Pulman, Andy; Taylor, Jacqui (JMIR Publications, 2012)
BackgroundThe Internet has revolutionized the health world, enabling self-diagnosis and online support to take place irrespective of time or location. Alongside the positive aspects for an individual's health from making use of the Internet, debate has intensified on how the increasing use of Web technology might have a negative impact on patients, caregivers, and practitioners. One such negative health-related behavior is Munchausen by Internet. ObjectiveMunchausen by Internet occurs when medically well individuals fake recognized illnesses in virtual environments, such as online support groups. This paper focuses on the aspect of Munchausen by Internet in which individuals actively seek to disrupt groups for their own satisfaction, which has not yet been associated with the wider phenomena of Internet trolls (users who post with the intention of annoying someone or disrupting an online environment). MethodsA wide-ranging review was conducted to investigate the causes and impacts of online identity deception and Munchausen by Internet drawing on academic research and case studies reported online and in the media. ResultsThe limited research relating to motivation, opportunity, detection, effects, and consequences of Munchausen by Internet is highlighted and it is formally linked to aspects of trolling. Case studies are used to illustrate the phenomenon. What is particularly worrying is the ease with which the deception can be carried out online, the difficulty in detection, and the damaging impact and potential danger to isolated victims. ConclusionsWe suggest ways to deal with Munchausen by Internet and provide advice for health group facilitators. We also propose that Munchausen by Internet and Munchausen by Internet trolling should be formally acknowledged in a revised version of the Diagnostic and Statistical Manual DSM-5. This will assist in effectively identifying and minimizing the growth of this behavior as more people seek reassurance and support about their health in the online environment. We also suggest directions for future research.